Pembinaan Masjid untuk Meningkatkan Kenyamanan Beribadah di Masjid Baitul Ma'mur Desa Dwi Karya Mustika - M Dimas Yudi Witjaksono; Fikriyan Anwar; Mahripal Ihsan; Danisa Rahmi Ramadina; Risqiyah Nurbaet (LPMP Imperium, 2024)
The student work program in community service as a form of mosque development in Dwi Karya Mustika Village, East Mesuji District, Mesuji Regency was carried out based on the orientation of student awareness of cleanliness around the village mosque environment to increase the community's comfort in worshiping. The subjects of assistance chosen were the caretaker and the community of Dwi Karya Mustika Village. The subjects were chosen because they saw that the condition of the mosque environment in Dwi Karya Mustika Village was still not clean. This has an impact on the condition of the mosque which is not well maintained. The method used in this service is to involve the active participation of the community and the mosque caretaker to develop awareness of cleanliness in the mosque environment of Dwi Karya Mustika Village. Through this participatory approach, it is hoped that the community and the caretaker of the Dwi Karya Mustika Village mosque can feel the positive impact of their contribution to cleanliness in the mosque environment so that the mosque becomes a comfortable place to carry out religious activities. The results of this service show the level of active participation of the community in the awareness and cleanliness of the mosque to maintain and provide comfort in worship.